PERANCANGAN KONSERVATORI MUSIK KONTEMPORER DI YOGYAKARTA DENGAN PENDEKATAN AKUSTIK DAN MUSIK - , RIZKA TIARA MAHARANI, Harry Kurniawan, ST, MSc. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The conservatory of contemporary music is a formal education institution which has specialized in field of contemporary music. This is an effort to support the govermentâs program which will expand the music formal education as well as develop music in creative industri. So, Yogyakarta as a base of creative region in Indonesia was elected as the right location of conservatory. The design of conservatory is a result from translation of music in a song. The song will be analyzed through music sheet by taking some music components and will be translated by the similarity between music and architecture. Beside that, some rooms are also designed with solve the problem of acoustic room.